This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
f ( x ) = x 3 − 3 ∣ x ∣ + 2 = { f + ( x ) = x 3 − 3 x + 2 f − ( x ) = x 3 + 3 x + 2 for x ≥ 0 for x < 0
For x ≥ 0 ,
x 3 − 3 x + 2 ( x − 1 ) ( x 2 + x − 2 ) ( x − 1 ) 2 ( x + 2 ) ⟹ x = 0 = 0 = 0 = 1
Solution x = − 2 < 0 is unacceptable.
For x < 0 , ⟹ f − ( x ) = x 3 + 3 x + 2 ⟹ f − ′ ( x ) = 3 x 2 + 3 > 0 for all x . Therefore, f ( x ) − is an always increasing function and it has only one solution. Let us check if the solution x < 0 . We note that f − ( − 1 ) = − 2 and f − ( 0 − ) = 2 , therefore the solution is − 1 < x < 0 .
Therefore, f ( x ) = x 3 − 3 ∣ x ∣ + 2 has 2 solutions.